P4 2 Maximus Gaseous Exhalius - Bakrania, Roshni; Hanna, Caitlin; Devenport, Hannah; Malkin, Oliver (Physics Special Topics, 2023)
In “The Adventures of Tintin” a float plane is used to fly across the desert, however, it runs low on fuel. In this paper, we use a similar model plane (Piper PA-18) to determine the plane’s overall energy efficiency given that it was refueled using a belch. We found the efficiency of the plane engine to be 0.814 % based on the fuel of choice being ethanol vapour and only a small amount (0.280 kg), which produced an energy of 1.93 kJ to keep the plane flying for a short period of time.